Seepage effect on failure mechanisms of the underwater tunnel face via CFD–DEM coupling. (June 2022) - Fu, Yanbin; Zeng, Deqi; Xiong, Hao; Li, Xuhui; Chen, Yuelong
Abstract: Seepage plays a significant role affecting the tunnel face failure process. However, its effect on the stability of the underwater tunnel face remains unclear. To study the seepage effect on the failure mechanism of the underwater tunnel face, this study models the failure process by the Computational Fluid Dynamics-Discrete Element Method (CFD–DEM) approach, in which the seepage force is simulated by fluid–particle interaction between CFD and DEM. The contact parameters of the sand particles in water were obtained by calibrating the results of underwater sand column collapse tests. In this study, three hydraulic conditions including dry, undrained, and seepage are considered for the tunnel face. The simulation results indicate that seepage affects the failure mechanism and the support pressure significantly. Then, a comparison between CFD–DEM results and solutions in previous literature was conducted, which suggests that the tunnel face permeability is the key factor that causes the difference in the support pressure under different hydraulic conditions. Additionally, failure mechanisms with different water depths were analyzed by displacement field, water pressure field, flow field, and support pressure. The results show that under the seepage conditions the failure zone is enlarged as the water depth increases. Besides, the microscopic contact information under the seepage condition in different regions was presented. This work provides evidence for evaluating the support pressure of a stable tunnel face when considering the seepage.